Functional Differentiation of BnVTE4 Gene Homologous Copies in α-Tocopherol Biosynthesis Revealed by CRISPR/Cas9 Editing - Zhang, Haiyan; Shi, Yuqin; Sun, Mengdan; Hu, Xuezhi; Hao, Mengyu; Shu, Yu; Zhou, Xue-Rong; Hu, Qiong; Li, Chao; Mei, Desheng (Frontiers in Plant Science, 2022)
Tocopherols are essential nutrient for the human health known as vitamin E. Vitamin E deficiency can have a profound effect on the human health, including the central nervous system, cardiovascular and immune protection. Multiple enzymatic steps involved in the conversion between different forms of tocopherols. Among them, γ-tocopherol methyltransferase encoded by gene VTE4 catalyzes the conversion of γ- to α-tocopherol or δ- to β-tocopherol isoforms. However, the gene copies and their functional contribution of VTE4 homologs in Brassica napus were not elucidated. To this end, different mutation combinations of four putative BnVTE4 homologous copies were generated by using CRISPR/Cas9 genome editing technology. Editing of those BnVTE4 homologs led to a significantly change the α-tocopherol content and ratio between α- to γ-tocopherol compared with wide type control. Analysis of the different combination of BnVTE4 edited homologs revealed that the contribution of BnVTE4 individual gene displayed obvious functional differentiation in α-tocopherol biosynthesis. Their contribution could be in order of VTE4.C02-2 (BnaC02G0331100ZS) > VTE4.A02-1 (BnaA02G0247300ZS) > VTE4.A02-2 (BnaA02G0154300ZS). Moreover, the VTE4.A02-1 and VTE4.A02-2 copies might have severe functional redundancies in α-tocopherol biosynthesis. Overall, this study systemically studied the different effects of BnVTE4 homologs, which provided theoretical basis for breeding high α-tocopherol content oilseed rape.